Infection Control Management and Compliance among Nurses in Selected Hospitals in Malaysia - Noor Hasliza, Che Seman (2022)
Nurses, as health care professionals, have the duty to ensure that their patients are free from any nosocomial infection that may happen, especially within 48 hours after post-administration in a hospital setting. The importance of knowledge, attitude, and hands-on practices may influence the nurses’ compliance towards infection control practices, especially among the Malaysian nurses from selected hospitals, in order to meet the challenges of protecting the patients who are receiving treatments. If these infections are prevented in the clinical environment, it will be able to help the patients with early recovery and obtaining high-quality medical care in the clinical setting. Hence, this study investigated the knowledge, attitudes, skill, and practices towards the compliance of infection control practices at a clinical location among the nurses from selected hospitals, with the aim of achieving the end safety treatment to patients' care. The study was conducted by involving nurses from selected local government and private hospitals. The study used a cross-sectional and survey questionnaire that analyzed factors related to knowledge, attitude, and practices. A total of 400 samples were obtained with stratified random sampling that focused on nurses who are practicing in Malaysian hospitals. Next, data analyses were done by using mean and standard deviations, followed by analysis with One-way ANOVA to test the hypotheses at <0.05 levels of significance respectively through the use of the Statistical Package for Social Science (SPSS) version 22.0. The main study population (n=400) was distributed with the questionnaires. Out of the 400 questionnaires distributed, 359 were returned with completed finding, hence 1% of the study population did not response to the survey. The results showed that 66.7% of the selected nurses had high knowledge in infection control practices, while 58% of them were positive toward the implementation of infection control practices. Gender (p=0.016) and the years of clinical working experiences (p=0.001) were found to significantly influenced attitudes. These findings indicated that there is knowledge, attitude and practice gap influences among Malaysian nurses. The results showed that the nurses in the selected hospitals demonstrated a moderate level of intention to work, with significant mean difference (mean diff=-0.287, p<0.05) was detected between the 21 to 25 years old and over 30 years old responses. Throughout the study finding, a state-wide survey was utilized to measure the IPC practice compliance among Malaysian nurses from the selected hospitals. These nurses were determined to be insufficiently performing in knowledge attitude towards compliance in infection control practices. The non-compliance skill practices among these Malaysian nurses may lead to infection breakdown, thus affecting patient safety in the hospital setting.